Pembahasan Kaidah Fikih Khusus dalam Ibadah Mahdah Berdasarkan Prinsip Tauqif dan Niat - Noor Halimah; Nabila Anggraini; Indra Hassbullah; Khairin Hafijhin; Lisnawati Lisnawati; M. Luthfi Setiarno (STIKes Ibnu Sina Ajibarang, 2025)
Mahdah worship holds a central position in Islamic teachings as a pure form of servitude to Allah SWT. Due to its tauqifi nature, the implementation of mahdah worship must strictly adhere to the provisions of the Sharia without additions or modifications. This study aims to examine and analyze specific fiqh principles that serve as guidelines in the practice of mahdah worship. A qualitative method with a library research approach was employed, through an in-depth review of classical and contemporary literature related to fiqh principles. The findings indicate that principles such as